Future Trends in Education Post COVID-19 Teaching, Learning and Skills Driven Curriculum - Al Naimiy, Hamid M. K.; Bettayeb, Maamar; Elmehdi, Hussein M.; Shehadi, Ihsan (Springer Nature Singapore : Imprint: Springer, 2023)
This open access book presents the proceedings of the first post COVID-19 conference on Education at the University of Sharjah, United Arab Emirates, on March 14-16, 2022. The book offers state-of-the-art approaches and methodologies in education post-COVID-19. It showcases emerging technology utilization in improving the quality of education, teaching and learning. It discusses the transformation of the curriculum, such as course design and delivery, assessment, and instructional methodologies that focus on employment readiness for the ever-evolving job market. Contributions include a wide range of topics such as online education, curriculum development, artificial intelligence, academic accreditation for hybrid & online learning. Given its scope, the book is essential reading for scholars, students, policy-makers, and education practitioners interested in a better understanding of technological innovations.